The Scenario of Higher Education Administration of Chinese Buddhist Order of Sangha in Thailand. - Pasanon, Phra Weerapong; WANGTHANOMSAK, MATTANA (Saengtham College Journal, 2023)
This research aims to identify the scenario of higher education administration of Chinese Buddhist Order of Sangha in Thailand. The study was conducted using Ethnographic Delphi Futures Research (EDFR) Method, and 19 experts were purposively selected and can be divided into 3 categories: 1) 7 senior executives (Phra Thera) of the Chinese Buddhist Order of Sangha. 2) 7 educational administrators of the Chinese Buddhist Order of Sangha and 3) 5 educational administrators of general higher education institutes. The instruments employed in this research were semi-structured. The statistics used in the study were: mode, median, interquartile range, and content analysis. The research findings reveled that: The scenario of higher education administration of Chinese Buddhist Order of Sangha in Thailand is as follows: 1) Philosophy of higher education of Chinese Buddhist Order of Sangha: maintaining and promoting the philosophy of Mahayana Buddhism in Thailand by encouraging young successors to have Mahayana Buddhism Ideology and inherit Chinese Buddhist Order of Sangha, 2) Vision and Goal of Higher education: set by the senior executives of the Chinese Buddhist Order of Sangha and establishing the higher education administration of Chinese Buddhist Order of Sangha as the institute of Chinese Culture and Art, focusing on developing morale of the learners, 3) University buildings : on the property of Chinese Buddhist Order of Sangha should be safe and secure, 4) Curriculum : approved by the Office of Higher Education Commission, focusing on Arts, Languages and Chinese cultures; 5) The development of Higher education administration, including systematic planning, proceeding and monitoring; 6) Budgeting: supported by Chinese Buddhist Order of Sangha in Thailand, Annual Kathina Ceremony, and also by the World Relations Organization of Buddhism; 7) Staffing: selecting the qualified executives from Chinese Buddhist Order of Sangha in Thailand; 8) Establishing the academic collaboration network and MOU for propagation of the content of the Mahayana Buddhism nationally and internationally; 9) Student admission nationally and internationally: accepting novices graduated from the Buddhist Dharma School of both Chinese Buddhist and Thai Sect, and also monks and priests from all religion with no age restriction; 10) Public relations: media through various channels such as website, television, radio, print media and through religion network nationally and internationally.